Integrating The Network Pharmacology and Molecular Docking Confirmed with In Vitro Toxicity to Reveal Potential Mechanism of Non–Polar Fraction of Cyperus rotundus Linn as Anti-Cancer Candidate - Susianti Susianti; Syaiful Bahri; Sutopo Hadi; Arif Setiawansyah; Lanang Rachmadi; Ibnu Fadilah; Maya Ganda Ratna (Journal of Multidisciplinary Applied Natural Science, 2025)
Cyperus rotundus Linn is a plant that is historically used in traditional medicine with anti-cancer potential. Despite the evidence of C. rotundus anti-cancer effect on various human carcinoma cell lines, its pharmacological mechanism remains unclear, particularly its non-polar fraction. This study was employed to provide mechanistic insight regarding the anti-cancer properties of C. rotundus non-polar fraction by integrating in silico and in vitro approach. The network pharmacology study was used to observe the molecular targets of n-hexane fraction of C. rotundus, confirmed by molecular docking simulation using Autodock 4.2. The in vitro toxicity using BSLT method was used to strengthen the in silico result. The network pharmacology investigation revealed several core targets including PI3K, MAPK1, mTOR, RAF1, and NF-κB in the potential anti-cancer mechanism of C. rotundus. The molecular docking study illustrated that compound 3 (Isopetasol) and compound 9 (alpha-cyperone) as the most promising compound in n-hexane fraction of C. rotundus, with free binding energies consistently less than -7 kcal/mol in all targets. The in vitro BSLT signified the in silico results, highlighting the highest toxicity of fraction 3 exhibited among others. Integrating the network pharmacology and molecular docking simulation along with in vitro toxicity have provided evidence of the anti-cancer potential of n-hexane fraction of C. rotundus. Specific compounds and the molecular targets responsible for its anti-cancer properties have been identified, warranting further investigations.